UV-VISIBLE SPECTROSCOPIC AND FTIR ANALYSIS OF SARCOSTEMMA BREVISTIGMA, WIGHT. AND ARN - Dhivya, S. M.; Kalaichelvi, K. (International Journal of Current Pharmaceutical Research, 2017)
Objective: Â The present study was carried out to characterize the bioactive constituents present in aerial parts of ethanolic extract of Sarcostemma brevistigma using UV-VIS and FTIR. Methods: Â FTIR spectroscopy is an established timeâ€saving method to characterize and identify functional groups. Results: Â The UV-VIS profile showed different peaks ranging from 200â€1044 nm with different absorption respectively. UV-VIS profile showed the peaks at 254.00 and 680.00 nm for flavonoid. FTIR spectra showed the peak at 3418.85 cm-1 for N-H group. FTIR analysis and UV-VIS analysis showed the presence of flavonoids and a phenolic compound. The FTIR spectra had amply evidenced the occurrence of OH group together with the Terpenoids, and Phenol. The FT-IR spectrum showed the presence of an amine (N-H), alkyl (C-H), nitrile (Câ‰¡N), halo formyl (C=O), alkenyl (C=C), hydroxyl (O-H), haloalkane (C-F), nitrates and carbonate compounds. Conclusion: Â The results confirm the fact that this plant posse's important bioactive constituent, so further scientific investigation is needed.